2022
DOI: 10.56338/jks.v5i1.2185
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor Risiko Kejadian Filariasis di Kecamatan Dolo Barat Kabupaten Sigi

Abstract: Filariasis adalah penyakit menular yang disebabkan infeksi cacing filaria, ditularkan melalui gigitan nyamuk yang menimbulkan pembengkakan pada tangan, kaki, glandula mamae, dan skrotum, serta dapat menimbulkan kecacatan seumur hidup apabila tidak mendapatkan pengobatan. Provinsi Sulawesi Tengah tercatat 193 kasus pada tahun 2021 dan kasus paling banyak terdapat di  kecamatan dolo barat kabupaten sigi dengan kasus tertinggi yaitu 14 kasus. Tujuan penelitian ini adalah untuk mengetahui Faktor Risiko Kejadian Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…This situation is to the results of research that houses with breeding places have a risk of 1,185 times compared to houses without breeding places (12). The same study showed that reeding place, resting place, knowledge, and attitude were variables that had a significant association with filariasis incidence in Semarang, as shown by their p-values and OR values (13).…”
Section: Breeding Place and Filariasis Occurrence In Sigi Regency's E...mentioning
confidence: 72%
“…This situation is to the results of research that houses with breeding places have a risk of 1,185 times compared to houses without breeding places (12). The same study showed that reeding place, resting place, knowledge, and attitude were variables that had a significant association with filariasis incidence in Semarang, as shown by their p-values and OR values (13).…”
Section: Breeding Place and Filariasis Occurrence In Sigi Regency's E...mentioning
confidence: 72%
“…In terms of physical environmental factors, research conducted in India shows that the presence of open drainage systems, such as U-ditches, and other mosquito breeding sites could amplify the risk of lymphatic filariasis by 24.6 times and 2.1 times, respectively (14). In addition, a study in Indonesia found that people who did not use bed nets at night were seven times more likely to develop lymphatic filariasis than those who did (15). Therefore, we further examine to understand the relationship between the sewerage conditions and the frequent use of mosquito nets and the incidence of filariasis in the community, especially in developing countries where filariasis remains endemic in some areas.…”
Section: Cite This Asmentioning
confidence: 99%
“…ITNs have been shown to decrease child mortality under the age of five by 20% from all causes in testing sites in African countries (49). For instance, bed nets with permethrin residue are highly recommended for the reduction of lymphatic filariasis (15). Since insect repellents in mosquito bed nets do not harm humans, they are not hazardous to health (7).…”
Section: The Presence Of Bed Netsmentioning
confidence: 99%
“…Filariasis (penyakit kaki gajah atau Elephantiasis) suatu penyakit menular menahun yang disebabkan oleh parasit cacing filaria yang hanya dapat ditularkan melalui kontak aktif nyamuk yang mengandung cacing filaria dalam tubuhnya. Dalam tubuh manusia, cacing tersebut tumbuh menjadi cacing dewasa dan menetap di jaringan limfe sehingga menyebabkan pembengkakan di kaki, tungkai, payudara, lengan dan organ genital (Astriana, Afni, Andri, & Yani, 2022).…”
Section: Pembahasanunclassified
“…Dengan demikian maka Indonesia juga akan mencapai eliminasi Filariasis. Untuk mencapai Eliminasi Filariasis tersebut perlu adanya pemahaman yang cukup serta menyeluruh tentang besarnya permasalahan Filariasis dan faktor risiko yang mempengaruhinya (Astriana et al, 2022).…”
Section: Pembahasanunclassified